Reconstruction of complex orbital fracture with titanium implants - Yi, Wen-Shu (International Journal of Ophthalmology Press, 2012)
AIM: To evaluate the effectiveness and safety of complex orbital fracture reconstruction with titanium implants. METHODS: A retrospective review of 46 patients treated with complex orbital fractures reconstruction using titanium implants from January 2005 to December 2008 was conducted. The following data were recorded: age, gender, mechanism of injury, preoperative and postoperative orbital CT, visual acuity, diplopia, ocular motility and Hertel exophthalmometer. RESULTS: The most common cause was motor vehicle accident (47.8%), followed by industrial injury (30.4%). All patients had improved appearance after operation and CT scan at one week after operation showed the fracture defects of orbit and neighboring areas had been reconstructed. Forty-six cases had various degrees of enophthalmos before operation. Among them, 32 cases were completely corrected, 11 cases improved obviously and 3 cases had no improvement after operation. Thirty-six patients with visual acuity ≥20/60 revealed diplopia of various degrees, including 26 patients had diplopia in right ahead and/or reading positions. At the sixth month after operation, diplopia disappeared in five patients, 7 patients still had diplopia in right ahead and/or reading positions, 14 patients had diplopia in positions rather than right ahead and reading positions (<20°) and ten patients had diplopia only at peripheral gazing (>20°). All patients had various degrees of ocular motility disorders before operation. At the sixth month after operation, eyeball movement disorder disappeared in 9 patients, 31 patients showed improvement and 6 patients had no improvement. Complications of implant infection, rejection and displacement were not reported after operation. CONCLUSION: The application of titanium implants in the repair of complex orbital fractures greatly improves the appearance and functional results, which is a favorable material for plastic surgery of complex orbital fracture.